The Role of Meaning in Life as a Moderator of the Relationship between Parental Acceptance, Religiosity, and Life Satisfaction in Parents of Children with Special Needs - Masyhuri, Masyhuri; Asra, Yulita Kurniawaty; Wahyuni, Sri; Lubis, Muhammad Drajad; Yerima, Youssoufa Harouna (Universitas Muhammadiyah Yogyakarta, 2026)
Parenting children with special needs can be a significant challenge, often causing stress and lowering parental life satisfaction. This study aims to analyze the role of meaning in life as a moderator of the relationship between parental acceptance, religiosity, and life satisfaction in parents of children with special needs. This study used a quantitative approach involving 400 parents of children with special needs in Riau Province. The instruments used included the Parental Acceptance and Understanding of Autistic Children Scale (PAUACS), a religiosity scale, the Meaning in Life Scale, and the Satisfaction with Life Scale. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results revealed that parental acceptance and religiosity had a positive and significant effect on life satisfaction, whereas meaning in life had no significant effect. In addition, meaning in life was not shown to moderate the relationships between parental acceptance and religiosity and life satisfaction. These findings indicate that increased life satisfaction among parents of children with special needs is more influenced by the ability to accept the child's condition and strengthening religiosity than by the moderating function of meaning in life. This means that support programs for parents of children with special needs should be more focused on strengthening parental acceptance and religiosity as strategies to improve their well-being and life satisfaction.